If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 3 = 6x + 2 Reorder the terms: 3 + x = 6x + 2 Reorder the terms: 3 + x = 2 + 6x Solving 3 + x = 2 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 3 + x + -6x = 2 + 6x + -6x Combine like terms: x + -6x = -5x 3 + -5x = 2 + 6x + -6x Combine like terms: 6x + -6x = 0 3 + -5x = 2 + 0 3 + -5x = 2 Add '-3' to each side of the equation. 3 + -3 + -5x = 2 + -3 Combine like terms: 3 + -3 = 0 0 + -5x = 2 + -3 -5x = 2 + -3 Combine like terms: 2 + -3 = -1 -5x = -1 Divide each side by '-5'. x = 0.2 Simplifying x = 0.2
| -36.838+10m=-2.3(-5.6m+6.5) | | 2y+72=180 | | (3p-2)(p+9)=0 | | h+9.5=-9.7 | | 25x^3+15x^2+2x=0 | | 3x+2(5x+4)=43 | | 7e^5x+8=0.23 | | 8x^2(2x+9)+(2x+9)=0 | | a/10-8=24 | | 5x+2x-3=17 | | 28-2c=6c+4 | | 12x^2-x=16x+40 | | 2p^2+6p+3=0 | | 180=(6x-19)+(3x+32) | | -4r^2+3+r=0 | | 2w+17=21+3w | | 12n+25=-35 | | 6r+4=5r-8 | | 6x-1=4x+27 | | 2y-16=y-6 | | 4r^3=r+3 | | (74x-67y)-(56x+8y)= | | 8x^2+45x+58=0 | | 4y+14=7y+1 | | -4.4s+6.2=8.8s | | 3a^2-6ab+3b^2=0 | | 3-2(3x+1)=3x-(x+3) | | 1.33*n=12 | | 1.33*10=12 | | ln(20)-ln(4)= | | f(x)=x^2+10x+15 | | a^2b-4abc+4bc^2=0 |